Development and Internal Validation of a Model Using Fecal Calprotectin in Combination with Infliximab Trough Levels to Predict Clinical Relapse in Crohn's Disease. Issue 1 (January 2017) - Roblin, Xavier; Duru, Gerard; Williet, Nicolas; Del Tedesco, Emilie; Cuilleron, Murielle; Jarlot, Camille; Phelip, Jean Marc; Boschetti, Gilles; Flourié, Bernard; Nancey, Stephane; Peyrin-Biroulet, Laurent; Paul, Stephane
Abstract : Background: The best noninvasive method predicting clinical relapse remains undetermined in infliximab (IFX)-treated patients with Crohn's disease. Methods: All patients with CD on IFX maintenance treatment and in clinical remission for at least 16 weeks, between 2011 and 2014, were enrolled in a prospective single-center study. The Crohn's Disease Activity Index (CDAI), fecal calprotectin, C-reactive protein levels, antibodies (ATI), and trough level (TLI) of IFX were measured at every IFX infusion. The best thresholds of TLI (2 versus 3 μg/mL) and calprotectin (50 versus 250 μg/g stools) were identified across four logistic regression models. Results: One hundred nineteen patients (mean age: 34 ± 12 yrs, mean disease duration: 7.8 yrs) were included. Mean follow-up was 20.4 months, and 17% of the patients were on IFX and azathioprine at inclusion. During follow-up, 37 patients (31.1%) relapsed, 78% within the first 6 months. The clinical characteristics of the relapsed and nonrelapsed patients were similar. After logistic regression, fecal calprotectin >250 μg/g stools (OR: 4.09; 95% CI, 1.01–16.21; P = 0.049) and TLI <2 μg/mL (OR: 14.85; 95% CI, 3.67–60; P < 0.0001) were associated with loss of response. A training cohort of 55 patients was isolated randomly to implement prediction rules for loss of response. The best predictive rules were the combination of a TLI <2 μg/mL and a fecal calprotectin level >250 μg/g stools (78.3%). These rules were validated on a test cohort of 64 patients with an accuracy of 87%, (sensitivity = 0.94, specificity = 0.84, positive predictive value = 0.73, and negative predictive value = 0.97). Conclusions: In IFX-treated patients with CD in clinical remission, a combination of TLI (<2 μg/mL) and fecal calprotectin (>250 μg/g of stools) is a good model for predicting loss of response. In contrast with previous data, low TLIs ranging from 2 to 3 μg/mL should neither systematically lead to the optimization of IFX use nor a switch in the treatment. Abstract : Supplemental Digital Content is Available in the Text.Article first published online 9 December 2016.